Genome-wide identification and bioinformatic analysis of PPR gene family in tomato - Ding, Anming; Li, Ling; Qu, Xu; Sun, Tingting; Chen, Yaqiong; Zong, Peng; Li, Zunqiang; Gong, Daping; Sun, Yuhe (Yíchuán, 2014)
Pentatricopeptide repeats (PPRs) genes constitute one of the largest gene families in plants, which play a broad and essential role in plant growth and development. In this study, the protein sequences annotated by the tomato (S. lycopersicum L.) genome project were screened with the Pfam PPR sequences. A total of 471 putative PPR-encoding genes were identified. Based on the motifs defined in A. thaliana L., protein structure and conserved sequences for each tomato motif were analyzed. We also analyzed phylogenetic relationship, subcellular localization, expression and GO analysis of the identified gene sequences. Our results demonstrate that tomato PPR gene family contains two subfamilies, P and PLS, each accounting for half of the family. PLS subfamily can be divided into four subclasses i.e., PLS, E, E+ and DYW. Each subclass of sequences forms a clade in the phylogenetic tree. The PPR motifs were found highly conserved among plants. The tomato PPR genes were distributed over 12 chromosomes and most of the